The Construction of Social Inequality Reality Among Characters in the Drama Pyramid Game - Afra Dini Ashshiddiq; Fajar Muharam; Haryo Windratno; Muhammad Anggi Azhar Pratama (Golden Ratio of Data in Summary, 2024)
This study examines the construction of social inequality among characters in the drama Pyramid Game using Peter Berger’s social construction theory and Charles S. Peirce’s semiotics. The research aims to analyze how visual and linguistic elements reflect social inequality between the characters. A descriptive qualitative analysis was employed, focusing on scenes depicting social inequality. The findings show that externalization is evident in actions and dialogues that demonstrate the enforcement of social rules and hierarchies. Objectivation is reflected in the shared acceptance of social inequality as a recognized reality, while internalization is observed in how the characters adapt to their roles within the social hierarchy. This study contributes to a deeper understanding of the dynamics of social inequality in the context of the drama.